Morphologic expression of the right coronary artery in horses. Comparative description with humans, pigs and other animal species - Gómez, Fabián A.; Ballesteros, Luis E.; Estupiñán, Hernando Y. (Austral Journal of Veterinary Sciences, 2017)
The objective of this research was to characterise morphologically the right coronary artery and its branches in the horse. The right coronary arteries of 120 horse hearts were perfused with semi-synthetic resin (85% Palatal GP40L; 15% styrene) and mineral red dye. The morphological and biometric characteristics of the right coronary artery and its branches (digital calibrator) were assessed. The diameter of the right coronary artery was 6.72 ± 2.58 mm. The interventricular subsinusal branch ended at the apex in 94 specimens (78.4%). The right circumflex branch originated at the site of intersection of the subsinnusal interventricular sulcus and the atrioventricular septum, extended along the coronary sulcus with a convoluted trajectory, ended at the obtuse edge of the heart or even at the anterior aspect of the left ventricle in 62 hearts (52.5%), and at the middle segment of the left ventricle in 42 cases (35.6%), whereas in 14 samples (11.9%) it ended at the adjacent surface of the left ventricle. The right conus branch was found in 98 specimens (81.6%) and in 2 of them (1.7%) it emerged directly from the right aortic sinus (third coronary artery). The hearts exhibited right coronary dominance in 118 specimens (98.3%) and in 2 specimens (1.7%) the coronary dominance was balanced. No myocardial bridges were observed. The high incidence of right coronary dominance observed in this study is consistent with previous studies. Due to its similarity with the human heart, we may ratify the equine model for procedural and hemodynamic applications.